Nadia LIE and Yolanda MONTALVO APONTE (editors). Literature and Money in Latin America. Brussels: Université de Liège, 200, 100pp (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
The Center for Hispanic American Studies at the University of Liege, Belgium, presents here some topics from the colloquium on literature and money in Latin America, presentations that emphasize the questioning between being a writer, what is written, and what should or should not be sold as written. In this framework, the dissociation made by writers between money and literature is substantial. Money, presented as an axis of power and at the same time corruption for man, engenders a new problem, that of being. The specificity of the authors in showing money as the functional axis of a system, and of an economic setup that supports governments, is the foreground of the discussion.